Digital Video Stabilization: Methods, Datasets, and Evaluation - Souza, Marcos Roberto e; Maia, Helena de Almeida; Pedrini, Hélio (Anais do Concurso de Teses e Dissertações da SBC (CTD-SBC); 2024: Anais do XXXVII Concurso de Teses e DissertaçõesDO - 10.5753/ctd.2024.1961, 2024)
Video stabilization removes shaky camera motion from videos. In our thesis, we presented an extensive review, including a formal problem defini tion, meta-analysis, and other elements, resulting in two survey papers. We introduced new measures for stability assessment and studied the correlation between them and human perception. We also proposed a novel evaluation ap proach for 2D camera motion estimation. We then introduced NAFT, a semi-online DWS method with a neighborhood-aware mechanism to stabilize without an explicit stability definition. We supervised NAFT with SynthStab, our pro posed synthetic dataset. NAFT closed the quality gap with non-DWS methods while reducing the number of parameters and model size by 14×.